Description of three new species of Larnaca Walker, 1869 (Orthoptera: Gryllacrididae: Gryllacridinae) from Xizang, China - Su, Jie; Duan, Yanhao; Li, Yonghui; Shi, Fuming (Zootaxa, 2024)
This paper reports three new species of the genus Larnaca Walker, 1869 from Xizang, China, i.e. Larnaca (Larnaca) rufifronta Su, Duan & Shi sp. nov., Larnaca (Larnaca) rubiabdomina Su, Duan & Shi sp. nov. and Larnaca (Larnaca) xizangensis Su, Duan & Shi sp. nov. The diagnostic illustrations are provided.